Medicine designed to combat diseases of affluence affects the early development of fish. How do plastic microparticles contribute? - Medkova, Denisa; Hollerova, Aneta; Blahova, Jana; Marsalek, Petr; Mares, Jan; Hodkovicova, Nikola; Doubkova, Veronika; Hesova, Renata; Tichy, Frantisek; Faldyna, Martin; Taştan, Yiğit; Kotoucek, Jan; et al. (Elsevier BV, 2023)
The incidence of diseases of affluence, such as diabetes mellitus, cardiovascular diseases, high blood pressure, and high cholesterol has been reported to rise. Consequently, the concentrations of residues of drugs designed to treat these diseases have been rising in water bodies. Moreover, the toxicity of these pharmaceuticals towards fish and other non-target organisms can be even enhanced by microplastic particles that are reportedly present in surface water. Therefore, the aim of this study was to describe the effects of three highly prescribed drugs, in particular metoprolol, enalapril, and metformin on fish early-life stages. Also, it was hypothesized that polystyrene microparticles will increase the toxicity of metoprolol to fish early-life stages. Embryonal acute toxicity tests on Danio rerio and Cyprinus carpio were carried out in order to describe the possible toxic effects of metoprolol, enalapril, and metformin. Also, the acute toxicity of polystyrene microparticles and the combination of metoprolol with polystyrene microparticles were tested on D. rerio embryos. Additionally, a 31-day long embryo-larval subchronic toxicity test was carried out with C. carpio in order to describe the long-term effects of low concentrations of metoprolol. The results of the study show that both metoprolol and enalapril have the potential to disrupt the early development of the heart in the embryonal stages of fish. Also, enalapril and metformin together with polystyrene microparticles seem to possibly disrupt the reproduction cycle and act as endocrine disruptors. Both pure polystyrene microparticles and the combination of them with metoprolol affect inflammatory processes in organisms. Additionally, metformin alters several metabolism pathways in fish early-life stages. The results of the study bring new evidence that even low, environmentally-relevant concentrations of pharmaceuticals have the potential to disrupt the early development of fish, particularly on a molecular level.
Keywords: Carps; Microplastics; Water; Metformin; Enalapril; Pharmaceutical Preparations; Animals; Polystyrenes; Plastics; Zebrafish; Water Pollutants, Chemical; Metoprolol; 3. Good health; 14. Life underwater